Alternative method to locate centre of rigidity in asymmetric buildings. - Basu, Dhiman
Response of asymmetric buildup under earthquake excitation often involves lateral vibration coupled with torsional vibration. Floor slab is, in general, assumed as rigid along the in-plane direction. Building code provisions to account for the torsional effect in static force procedure are based on centre of rigidity or shear centre of the building. A convenient procedure is developed here to locate the centre of rigidity or shear centre, which can be implemented, using any standard building analysis software. The procedure is applicable for orthogonal as well as non-orthogonal building systems and accounts for all possible definitions of static eccentricity to compute the design response. An irregular building is analysed to illustrate the proposed methodology. Significant variation in member force resultants is observed due to different definitions of static eccentricity. Finally, a mathematical proof is presented to substantiate the applicability of the proposed procedure to a non-orthogonal building.
Keywords: Buildings; Earthquake; Earthquake-resistant design; Seismic analysis; Torsion